2006
DOI: 10.1116/1.2162563
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence in the silicon-oxygen system

Abstract: The luminescent properties of SiOx ranging in composition between x=0 and x=2 are presented. Luminescence in the SiOx system is found to be tunable across the full visible spectrum and into the near infrared. The data are used to generate an emission color map for the complete SiOx system. At the lower annealing temperatures, several lines of evidence suggest that the luminescence is due to the presence of amorphous silicon nanoclusters, whereas for higher annealing temperatures the emission is dominated by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
5
20
1
Order By: Relevance
“…This is similar to the case for amorphous silicon, which is generally reported to have two or three lifetime components ranging from 1 ms to as much as 1 ms [14,15]. As we reported recently [17], the temperature dependence of the integrated intensity of this peak increased by 4-5 on going from 4 to 300 K and showed a saturation behavior near 20 K-also consistent with investigations of amorphous silicon films [18] and amorphous porous silicon [19]. Having established that the PL has many characteristics similar to amorphous silicon, we attempted to model the spectrum assuming that the PL originates from amorphous silicon nanoparticles.…”
Section: Resultssupporting
confidence: 84%
“…This is similar to the case for amorphous silicon, which is generally reported to have two or three lifetime components ranging from 1 ms to as much as 1 ms [14,15]. As we reported recently [17], the temperature dependence of the integrated intensity of this peak increased by 4-5 on going from 4 to 300 K and showed a saturation behavior near 20 K-also consistent with investigations of amorphous silicon films [18] and amorphous porous silicon [19]. Having established that the PL has many characteristics similar to amorphous silicon, we attempted to model the spectrum assuming that the PL originates from amorphous silicon nanoparticles.…”
Section: Resultssupporting
confidence: 84%
“…17À19 In these systems, ncSi size-control is usually achieved by changing the SiO x composition and peak thermal processing temperature. 19,34 In SiO x /SiO 2 superlattices, an additional size control strategy has been developed, involving the spatially confined growth of ncSi within the SiO x layers. 35 Using controlled evaporation deposition techniques, it was found that the size of ncSi was dependent on SiO x layer thicknesses ranging from 2 to 7 nm, with thicker layers giving rise to larger ncSi.…”
Section: Articlementioning
confidence: 99%
“…1d). [14] Having established the presence of luminescent silicon nanocrystals in thermally processed HSQ thin films, it was necessary to demonstrate the fabrication of structures that exploit the benefits of this method. These advantages include: first, unlike for deposition-based methods, both thin films and macroscopic quantities of nc-Si/SiO 2 can be readily produced.…”
mentioning
confidence: 99%